Pengaruh Profitabilitas, Pertumbuhan Penjualan dan Ukuran Perusahaan Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2012-2017 - Tiara Saumy Evant; Yolandafitri Zulvia (Jurnal Ecogen, 2019)
This study aims to examine the effect of profitability, sales growth, and firm size on dividend policy in manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX). This type of research is associative research. The population in this study is the manufacturing companies in the consumer goods industry sector registered on IDX for the period 2012-2017 with sampling using a purposive sampling technique. Samples were obtained by 16 companies from 42 study populations. Data was obtained from ICMD companies and financial statements of manufacturing companies in the consumer goods industry sector through the IDX website. The data analysis technique used is multiple regression analysis. To test the hypothesis using the t test. The results showed that profitability had a positive and significant effect on dividend policy in the consumer goods industry sector companies on the IDX, while sales growth had a negative and not significant effect on dividend policies in the consumer goods industry sector companies on the IDX. Meanwhile, firm size has a positive and significant influence on dividend policy on consumer goods industry sector companies listed on the IDX.Keywords: profitability, sales growth, firm size, and dividend policy